Comfortable experiences in nature accommodation: Perceived service quality in Glamping. (March 2017) - Brochado, Ana; Pereira, Cristina
Abstract: Glamping – a combination of the words 'glamour' and 'camping' – is an emergent concept in camping that combines comfort with direct contact with nature. This paper seeks to contribute to a better understanding of consumers' perceptions of services provided by glamping facilities. A measurement tool, GlampingExp – Glamping Experience, was developed for this purpose using a mixed methods approach that combines qualitative and quantitative research. Portugal is the target for this study. A content analysis of guest reviews was performed first, followed by in-depth interviews with glamping managers, in order to develop a battery of items to assess glamping experiences from the guests' perspective. A quantitative survey (N =166) was then conducted. Exploratory factor analysis revealed that service quality in this sector is multidimensional, including five facets: tangibles, staff, nature-based experiences, food and activities. A better understanding of clients' evaluations has strategic implications for any services designed to meet guests' needs. Therefore, this paper expands the existing body of research on glamping, focusing on guests' perspectives on dimensions of service quality in this type of accommodation. Management Implications: 1. The present study has important implications for managers of glamping facilities. 2. Managers can use the measurement tool, GlampingExp – Glamping Experience, to assess their performance based on their score for each dimension, as follows: tangibles, staff, nature-based experiences, food; and activities. 3. In order to match the guests' concept of glamorous camping, eco-tangibles are of utmost importance. 4. As extra activities and food are a component of good experiences, facilities need to provide package offers to guests. 5. Properties should provide nature-based experiences that offer guests a relaxing, tranquil stay in an authentic setting. Guests also value the hospitality of the staff.